2018
DOI: 10.1038/s41598-018-30978-6
|View full text |Cite
|
Sign up to set email alerts
|

Novel oncogenic and chemoresistance-inducing functions of resistin in ovarian cancer cells require miRNAs-mediated induction of epithelial-to-mesenchymal transition

Abstract: Resistin plays a role in the growth, proliferation, angiogenesis, metastasis and therapeutic resistance in different cancers. However, such effects of resistin have never been evaluated in ovarian cancer, a deadly gynecological malignancy. We observed a significant induction of ovarian cancer cells’ growth, invasion and cisplatin resistance, and established a mechanism of resistin action that included induction of EMT and stemness, as evidenced by down-regulated epithelial marker e-cadherin and up-regulated me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 32 publications
(40 reference statements)
0
24
0
Order By: Relevance
“…This cytokine induced platinum resistance, EMT, and stemness in vitro and in vivo by binding Toll-like receptor-4 (TLR4), and by stimulating the NF-κB-STAT3 pathway [119]. Moreover, STAT3 expression was associated with platinum resistance in EOC cells [120].…”
Section: Emt and Chemotherapy Resistancementioning
confidence: 99%
“…This cytokine induced platinum resistance, EMT, and stemness in vitro and in vivo by binding Toll-like receptor-4 (TLR4), and by stimulating the NF-κB-STAT3 pathway [119]. Moreover, STAT3 expression was associated with platinum resistance in EOC cells [120].…”
Section: Emt and Chemotherapy Resistancementioning
confidence: 99%
“…Liu's study found resistin could signi cantly increase ovarian cancer cell growth, colony formation, and invasion in 72 h. The IC50 of 25 ng/ml resistin + 2.5µM cisplatin group was about three times that of 2.5µM cisplatin group. While the growth of ovarian cancer cell was increased over three times by 25 ng/ml resistin in 72h [23]. So resistin could signi cantly increase ovarian cancer cells proliferation might partly due to that resistin decreased cisplatin-induced cytotoxicity.…”
Section: Discussionmentioning
confidence: 92%
“…Besides targeting BECLIN 1, miR20a also targets ATG16 in breast cancer [107] , while miR376b also targets ATG4 in breast cancer [105] . Let-7a is a tumor suppressor miRNA known to down-regulate the RAS oncogenic pathway in a variety of cancers, and its high expression correlates with chemo-responsiveness, low invasiveness, and better survival in ovarian cancer patients [110,111] . In ovarian cancer, this miRNA was shown to prevent the formation of autophagosomes by targeting ATG4 (the LC3 processing enzyme), ATG9A, and ATG16L [94] .…”
Section: Non-coding Rnas Regulation Of Autophagy In Cancers Affectingmentioning
confidence: 99%